Retrocolic Gastrojejunostomy After Pancreaticoduodenectomy: A Satisfactory Delayed Gastric-Emptying Rate. Issue 4 (April 2019) - Miyazaki, Yoshihiro; Oda, Tatsuya; Shimomura, Osamu; Enomoto, Tsuyoshi; Akashi, Yoshimasa; Hisakura, Katsuji; Ohara, Yusuke; Kimura, Sota; Hashimoto, Shinji; Ohkohchi, Nobuhiro
Abstract : Objectives: Delayed gastric emptying (DGE) is a critical complication after pancreaticoduodenectomy (PD). Antecolic gastrojejunostomy has long been adopted as standard procedure because it is thought to reduce DGE. However, we have used retrocolic gastrojejunostomy (retro-GJ) for more than 10 years and have not observed high DGE rates. We aimed to clarify whether our retro-GJ approach produced comparable outcomes in preventing DGE. Methods: A total of 211 patients who underwent pylorus-resecting PD with retro-GJ at our institution between 2005 and 2016 were retrospectively analyzed. The incidence rate of DGE and the length of postoperative hospital stay were assessed. Results: The overall incidence of DGE with our retro-GJ procedure was 13% (n = 28), and the rate of clinically relevant DGE (grade B or C based on the International Study Group of Pancreatic Surgery criteria) was 4% (n = 8). The median postoperative hospital stay was 17 days (interquartile range, 13–25 days). Major complications (Clavien-Dindo grade ≥III) occurred in 37% (n = 79) of patients and were not associated with the occurrence of clinically relevant DGE ( P = 0.47). Conclusions: Our retro-GJ approach after PD with gastrojejunostomy, which involves careful positioning at the left-sided inframesocolic point, satisfactorily prevents DGE.